Athletic training and sports medicine an intergrated approach - Starkey, Chad 1959 - (World Headquaters, 2013)
Written in cooperation with the American Academy of Orthopaedic Surgeons (AAOS), Athletic Training and Sports Medicine: An Integrated Approach, Fifth Edition is a multi-purpose, multi-course text that emphasizes the post-injury management techniques used by athletic trainers and physicians in management of orthopaedic injuries. This classic text now includes a sub-title to more accurately reflect the topical coverage of injury management and care.